ANALISIS PENGARUH PENGGUNAAN ARTIFICIAL INTELEGENCE (AI) CHATBOT GEMINI DALAM MENYUSUN PERANGKAT AJAR BAGI MAHASISWA PROGRAM PROFESI GURU CALON GURU (PPG-CG) - Dewa Nyoman Oka; Ni Nyoman Serma Adi; Ni Made Serma Wati (Widyadari, 2025)
This study examines the analysis of the influence of the use of Artificial Intelligence (AI) Gemini in compiling teaching devices for students of the Prospective Teacher Professional Program. This study uses a quantitative data analysis method, with a Statistical Description data analysis technique using the Rasch model assisted by the Winstep Application. While for the construct test from experts using Gregory analysis. The study was conducted at the IKIP Saraswati Teacher Training Institute using research subjects, namely students of the Prospective Teacher Professional Program, while the object of the study was the analysis of the use of Artificial Intelligence (AI) Gemini to compile teaching devices. The results of the analysis show that the Use of Artificial Intelligence (AI) Chatbot Gemini has an effect on Compiling Teaching Devices for Prospective Teacher Professional Program Students. With Person measure = 2.45> 0.0, Cronbach's alpha value of 0.92 and the person reliability value shows the number 0.94. While the expert validation results are 0.90 which is in the very high category which confirms that AI Gemini helps prospective teacher professional students in creating teaching devices.